Exploring the prognostic value of combined assessment of bone marrow plasma cell morphology, Vitamin D, and interleukin-6 in multiple myeloma - Huang, Ping; Zhang, Fenping; Lin, Yuchun; Peng, Jie; Yang, Zesong (Frontiers in Medicine, 2025)
ObjectiveThe study aims to explore the prognostic assessment value of bone marrow plasma cell morphology, Vitamin D (Vit D), and Interleukin-6 (IL-6) in patients with Multiple Myeloma (MM), with the potential to provide local medical care for follow-up patients and indirectly alleviate the difficulty of accessing healthcare in higher-level hospitals.MethodsClinical data were collected from 111 MM patients admitted to the Department of Hematology, The First Affiliated Hospital of Chongqing Medical University, between January 2022 and December 2024. The morphological characteristics of plasma cells in different stages of the disease were analyzed in patients with poor prognosis. The correlations between the number of plasma cells, Vit D, IL-6, laboratory indicators, and disease stages were investigated. Receiver Operating Characteristic (ROC) curves were plotted based on follow-up data to assess the prognostic value of these three indicators in MM.ResultsThe heterogeneity of plasma cell morphology is evident in MM patients, and there are significant differences in the number of plasma cells between the Durie-Salmon Staging System (DS) and the International Staging System (ISS) (p < 0.05). There were marked differences in bone marrow plasma cell count, Vit D levels, and IL-6 levels across different stages (p < 0.05). The number of bone marrow plasma cells and IL-6 levels before chemotherapy were significantly higher than those after chemotherapy, with statistically significant differences (p < 0.05). Vit D positively correlated with Serum Albumin (ALB) (r = 0.581, p < 0.05), while IL-6 negatively correlated with Hemoglobin (HGB) (r = −0.556, p < 0.05). The number of bone marrow plasma cells and IL-6 levels positively correlated with DS stages in MM patients (r = 0.4466, 0.6347, p = 0.0001, <0.0001, respectively). Vit D negatively correlated with DS stages in MM patients (r = −0.6312, p < 0.0001). The combined detection AUC of 0.835 was superior to that of IL-6 (z = 2.148, p = 0.032) and Vit D (z = 1.978, p = 0.042) alone.ConclusionCombined detection of bone marrow cellular morphology, Vit D, and IL-6 can provide effective prognostic monitoring for MM patients, potentially offering local follow-up care, reducing economic burdens, and improving quality of life.